2009
DOI: 10.3201/eid1509.090091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Foot-and-Mouth Disease Viruses, Ethiopia, 1981–2007

Abstract: Virus diversity indicates a virus reservoir in this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
171
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(195 citation statements)
references
References 31 publications
20
171
1
Order By: Relevance
“…Five of the seven serotypes of FMDv (O, A, C, SAT 2, SAT 1) are endemic in Ethiopia (Rufael et al, 2008;FAO, 2007;Ayelet et al, 2009;Negusssie et al, 2010). Studies undertaken on FMD so far revealed the existence of the disease in different parts of the country, with prevalence that vary from 8.18% in south Omo (Molla et al, 2010) to 44.2% in different parts of the country (Negusssie et al, 2010) and posing a major threat to cattle in many parts of the country, thereby causing considerable economic losses through morbidity, mortality and trade restriction.…”
Section: Introductionmentioning
confidence: 99%
“…Five of the seven serotypes of FMDv (O, A, C, SAT 2, SAT 1) are endemic in Ethiopia (Rufael et al, 2008;FAO, 2007;Ayelet et al, 2009;Negusssie et al, 2010). Studies undertaken on FMD so far revealed the existence of the disease in different parts of the country, with prevalence that vary from 8.18% in south Omo (Molla et al, 2010) to 44.2% in different parts of the country (Negusssie et al, 2010) and posing a major threat to cattle in many parts of the country, thereby causing considerable economic losses through morbidity, mortality and trade restriction.…”
Section: Introductionmentioning
confidence: 99%
“…The serological match of the field isolates to A ERI 98 could be attributed to the topotype similarities which suggest that there is close relationship between field isolate and the vaccine strain. But the low 'r' value recorded with the vaccine strain of A Iran 2005 and A22 IRQ suggest that the field isolate is so different from the vaccine strain that the vaccine is unlikely to protect (Ayelet et al, 2009).…”
Section: Foot-and-mouth Disease Is An Endemic Disease In Westmentioning
confidence: 99%
“…These include serotypes O, A, SAT 1 and SAT 2 and each serotype has many subtype variants. This antigenic variation is a cause of major setback in the control of FMD, as infection or vaccination with one serotype of FMDV does not protect against other serotypes and may fail to confer protection against other subtypes within the same serotype (Ayelet et al, 2009). The disease is caused by a small positive sense ssRNA virus (approx.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations